ANALYSIS OF THE QUALITY OF PUBLIC SERVICES IN DPPPAKB PASURUAN CITY - Ely Ibrahim; Meilissa Ike Dien Safitri (Journal of Governance and Global Studies, 2024)
This study aims to determine the quality of public services in a government, namely the Office of Women's Empowerment, Child Protection, and Family Planning of Pasuruan City. This research method is descriptive qualitative. Descriptive qualitative research is research that describes and describes phenomena and events that occur in the field and presents data factually, systematically, and accurately. Data collection is done by observation, interview and documentation. Data analysis in this study is by data reduction, data presentation, and conclusion drawing. The results showed that public services carried out by the Pasuruan City Office of Women's Empowerment, Child Protection, and Family Planning were related to employee awareness, the existence of rules, organizational factors, facility factors, and factors of ability and skills of human resources which were said to be running well. The results showed that the quality of public services in the Office of Women's Empowerment, Child Protection, and Family Planning of Pasuruan City has implemented five dimensions, namely Tangibel, Reliability, Responsiveness, Assurance, and Empathy.